Australian Company Financial Reporting: 1990. - Coda, Bernard A.; Moriarity, Shane R. (The Accounting Review, 1992)
Reviews the book `Australian Company Financial Reporting: 1990,' by J.B. Ryan, B.H. Andrew, M.J. Gaffikin and T. Heazlewood.